OPTIMIZATION OF PROCESS PARAMETERS FOR BIOSYNTHESIS OF CELLULASE BY CLADOSPORIUM CLADOSPORIOIDES USING AGRO WASTES - ISAIE MUSHIMIYIMANA; PADMAVATHI TALLAPRAGADA (International Journal of Pharma and Bio Sciences, 2013)
Cellulases play an important role in biomass utilization. Many fungi produce cellulases with high activities. The aim of this study is to describe the optimization of process parameters for the production of extracellular carboxymethyl cellulase (CMCase) by Cladosporium cladosporioides. Cellulase production was carried out using different agro wastes as substrates like potato peel, onion peel, carrot peel and sugar beet peel. The enzyme produced and its activity was determined under different process parameters like incubation period, pH, temperature and effect of carbon and nitrogen sources. A submerged type of fermentation was carried out for the enzyme production with the substrate concentration of 5.8 % (w/v) along with ammonium nitrate of 0.8% w/v as nitrogen source. The highest cellulase activity was observed with potato peel on 6th day and for onion peel, carrot peel and sugar beet peel was on 7th day of incubation. The highest cellulase activity was observed with sugar beet at the pH of 5.5 (1.56 U/ml) and at temperature 30ºC (1.65U/ml). With different carbon and nitrogen sources, the highest enzyme activity was observed with maltose and sugar beet as substrate (2.24U/ml) and with urea and onion peel as substrate (2.45U/ml).